“Baju Anti Buta Huruf” Learning Media to Improve Pre-Reading Skills in Early Childhood - Faridah; Mohammad Syaifuddin; Mohammad Syahri (Jurnal Ilmiah Pendidikan Profesi Guru, 2025)
Early literacy is a fundamental ability that serves as the foundation for children to develop reading skills at subsequent educational stages. However, many young children still experience difficulties in letter recognition, resulting in slow and suboptimal early literacy development. This study aims to analyze, develop, and evaluate the feasibility and effectiveness of the “Baju Anti Buta Huruf” learning media as an innovative alternative for improving early literacy in early childhood education. This study employed a Research and Development (R&D) method using the ADDIE development design. The research subjects consisted of 15 early childhood learners, who also served as the trial participants for the developed media. Data were collected through questionnaires for validation by subject matter experts, media experts, and early childhood teachers. Quantitative data analysis was conducted using a paired sample t-test to determine differences in early literacy abilities before and after the implementation of the learning media. The results indicate that the “Anti-Illiteracy Shirt” media is feasible and effective in improving early literacy skills, as evidenced by increased student interest, active participation, and improved letter recognition through multisensory activities involving body movement and visual symbol representation. The study concludes that the “Baju Anti Buta Huruf” media is a creative and effective alternative for enhancing early literacy skills in young children and supports teachers in implementing interactive learning strategies. The implications of this study suggest that early literacy instruction is more effective when designed using a multisensory approach that integrates visual, kinesthetic, and direct experiential elements.